Gastrostomy in Hospitalized Patients with Acute Stroke: NoroTek Turkey Point Prevalence Study Subgroup Analysis - Topcuoglu, Mehmet Akif; Ozdemir, Atilla Ozcan; Aykac, Ozlem; Milanoglu, Aysel; Gokce, Mustafa; Bavli, Songul; Arsava, Ethem Murat (Galenos Publ House, 2022)
Objective: Nutritional status assessment, dysphagia evaluation and enteral feeding decision are important determinants of prognosis in acute neurovascular diseases. Materials and Methods: NoroTek is a point prevalence study conducted with the participation of 87 hospitals spread across all health sub regions of Turkey conducted on 10-May-2018 (World Stroke Awareness Day). A total of 972 hospitalized neurovascular patients [female: 53%, age: 69 +/- 14; acute ischemic stroke in 845; intracerebral hematoma (ICH) in 119 and post-resuscitation encephalopathy (PRE) in 8] with complete data were included in this sub-study. Results: Gastrostomy was inserted in 10.7% of the patients with ischemic stroke, 10.1% of the patients with ICH and in 50% of the patients with PRE. Independent predictors of percutaneous endoscopic gastrostomy (PEG) administration were The National Institutes of Health Stroke Scale score at admission [exp (ss): 1.09 95% confidence interval (CI): 1.05-1.14, per point] in ischemic stroke; and mechanical ventilation in ischemic [exp (ss): 6.18 (95% CI: 3.16-12.09)] and hemorrhagic strokes [exp (ss): 26.48 (95% CI: 1.36-515.8)]. PEG was found to be a significant negative indicator of favorable (modified Rankin's scale score 0-2) functional outcome [exp (ss): 0.032 (95% CI: 0.004-0.251)] but not of in-hospital mortality [exp (ss): 1.731 (95% CI: 0.785-3.829)]. Nutritional and swallowing assessments were performed in approximately two-thirds of patients. Of the nutritional assessments 69% and 76% of dysphagia assessments were completed within the first 2 days. Tube feeding was performed in 39% of the patients. In 83.5% of them, tube was inserted in the first 2 days; 28% of the patients with feeding tube had PEG later. Conclusion: The NoroTek study provided the first reliable and large-scale data on key quality metrics of nutrition practice in acute stroke in Turkey. In terms of being economical and accurate it makes sense to use the point prevalence method.
Hastanede Yatan Akut İnmeli Hastalarda Gastrostomi: “NöroTek” Türkiye Nokta Prevalans Çalışması Alt Grup Analizi
Keywords: Stroke; intracerebral hemorrhage; malnutrition; dysphagia; flash mob